Correlation between air pollution and the spread and development of COVID-19 related disease - Marčenko, Erik (Strojniški vestnik, 2022)
Potential correlation of exposure to polluted air and the spread and co-development of COVID-19 and severe acute respiratory syndrome, caused by SARS-CoV-2 coronavirus, was examined. The emphasis was given on polluted air in the form of suspended particulate matter or liquid particles in gas or air (so-called dust particles). This study was structured as a systematic literature review of multiple research projects carried out across the globe. Impact of the polluted air particles on the virus spread was examined from the temporal and spatial spread. Furthermore, overall impact of particulate matter and COVID-19 disease on human health human was investigated on a microbiological level. Despite some ambiguity, through systematic literature review effect of the polluted air on the increased spread of various viruses was demonstrated. Longer exposure to contaminated airborne dust particles has a negative effect on the human immune system and in the case of infection with COVID 19, may even overload it. This can lead to serious consequences for human health or even cause death.This review article also provides an insight into a more comprehensive analysis of possible correlation between the spreading the virus (SARS-CoV-2) by means of particulate matter and other meteorological variables (such as air temperature and humidity, weather events and climate).
Keywords: air pollution; air quality; coronavirus; COVID-19; kakovost zraka; koronavirus; meteorological parameters; meteorološki parametri; morbidity; obolevnost; odziv imunskega sistema; onesnaževanje zraka; particulate matter; trdni delci; umrljivost